The Unintended Consequences of Employer Credit Check Bans for Labor Markets - Cortés, Kristle R.; Glover, Andrew; Tasci, Murat (The Review of Economics and Statistics, 2022)
Over the past fifteen years, eleven states have restricted employers' access to the credit reports of job applicants. We estimate that county-level job vacancies have fallen by 5.5% in occupations affected by these laws relative to exempt occupations in the same counties and national-level vacancies for the same occupations. Cross-sectional heterogeneity suggests that employers use credit reports as signals of a worker's ability to perform the job: vacancies fall more in counties with a large share of subprime residents and less for occupations with other commonly available signals. Vacancies fall most for occupations involving routine tasks, suggesting that credit reports contain information relevant for these types of jobs.